Havana and the Atlantic in the sixteenth century - Fuente, Alejandro de la (Envisioning Cuba, 2008)
The port : shipping and trade -- The fleets and the service economy -- Urban growth -- Production -- Slavery and the making of a racial order -- The people of the land